On convergence and stability of adaptive active noise control systems - Pawełczyk, M. (Archives of Acoustics, 2006)
The problems of convergence and stability of adaptive active noise control systems with the Filtered-Reference LMS algorithm are discussed. First, the assumptions required to derive convergence conditions are collected and addressed. Then, it is demonstrated that feedback systems are subject to convergence conditions different than those used for feedforward systems. Moreover, the problems of convergence of the adaptation algorithm and stability of the structural feedback loop are coupled. Theoretical considerations are supported by simulations experiments.